EXAMINATION OF USE OF WATER AND SOIL RESOURCES IN TERMS OF URBAN SUSTAINABILITY - (:unkn) unknown (ISEC PRESS, 2016)
Cities are the organization of collective consumption and of welfare delivery and are the major consumers of renewable and non-renewable resources. The rapid urbanization process and its chaotic problems such as drastic urbanization and ecological challenges have been phenomenal. As the population rapidly rises in the world, the requirements for water resources also increase for various reasons at the same time. On the other hand, global warming, greenhouse effect and degradation of forests make worse the situation. However, these negative consequences show how we are going to face the tragic problems for the next two or three decades. While the term of sustainability is defined and connected only with the environment now it is explained with a comprehensive term undertaking not only the environment but also the social, economic, cultural and governance aspects of cities. Sustainability has been discussed at various meetings for years such as the UN meeting the Earth Summit which took place in Rio in 1992 and emphasized that cities should be liveable in terms of costs, social equity and the ecology, which are the three major principles of sustainable development, but concrete and applicable results have not been achieved yet. In this study use of basic resources in particular water and soil will be analysed and examined based on sustainability and its major components such as economic, sociologic, ecologic within the limits of the paper. The study will also be evaluated through the balance of protection and use of resources considering certain samples in the context of Marmara Watershed in Turkey and Istanbul in particular. Literature reviews, quantitative and qualitative information, reports prepared by the institutions, statistics, and observations have been chosen and used as the method. Solutions and proposals will also be suggested based on the findings.
Keywords: Urbanization; Ecosystem; Watershed planning; Water resources; Sustainable use; Tragic problems